Pemahaman Awak Kapal dan Manajemen dalam Penerapan ISM Code pada Perusahaan Agensi Awak Kapal - Arubusman, Dian Artanti; Siregar, Chorry Imelda; Najoan, Denny; Saputra, Datep Purwa; Setyawati, Aswanti (Institut Transportasi dan Logistik Trisakti, 2023)
The purpose of the research is to find out and analyze the suitability of the crew and management perception related to work safety, protection of the marine environment and implementation of the ships’ operation using the International Safety Management Code in PT. Lautan Jaya Hasana. The main problem of the research is the lack of understanding and awareness of the crew and management of the importance to implement the ISM Code for work safety and to protect the marine environment. The ISM Code has not been implemented properly. This study used a Descriptive Qualitative method. There were 20 statements on understanding variables and actual implementation variables that were tested for validity and reliability. The samples were taken from 35 crew members from two types of bulk carriers by conducting in-depth interview with the crew members and the management employees. The result shows that most of the crew members, including the captain and the management of the company perform the same perception regarding the work safety, the protection of marine environment and the implementation of the International Safety Management Code for ships operation with a significant average difference and a perceived value of 9.20 between perceived understanding and actual implementation.